Integration of multiple ultra-capacitor banks in DC microgrid part I - Ahamad Fareed (2019)
DC Microgrid (Mg) is a small-scale power supply network that is designed to provide power to DC loads. It is an efficient and economical energy system comprising of different renewable sources and storages that are interconnected to meet the power demand from the load. Energy Storages (ES) are used in the DC Mg to mitigate the differences between the load demand and the generations. One such ES is the ultracapacitor bank (UC). An example of its application is to compensate the power deficiency or surplus during motor starting and shutting down to ensure system power quality. However, with increased load demand mounting, a single UC is no longer feasible to simultaneously provide for all the possible loads and to maintain long-term operation. Therefore, there is a need to configure multiple UC banks in the DC Mg for economic operation of the entire system.